IMPLEMENTASI CROSS LAYER ENCHENCHED PACKET SCHEDULING PAKET MULTIMEDIA UNTUK JARINGAN OFDM UPLINK DI BAWAH REDAMAN HUJAN - Kalimuddin, Dylan Adhytia; Riza, Oxy Primasetya; Kurniawan, Tri Wahyu (Program Kreativitas Mahasiswa - Penelitian, 2013)
In the previous network, optimization is often done on a separate layer and the result is less than optimal. Therefore, developed a new scheme to combine multiple layers of network protocol called Cross-Layer, for example in the physical layer and link layer. In this final project will be evaluated applying Cross-Layer Optimization methods with emphasis on the evaluation of scheduling schemes of OFDM uplink transmission of multimedia data packets using Enhanced Cross-Layer Packet Scheduling (CEPS) under rain attenuation. The results showed that the use of scheduling CEPS give effect to video and voice traffic is real-time priority in scheduling and packet loss and delay as small as possible while the data traffic (FTP) with a delay that can be tolerated can log buffer considering fairness and physical layer conditions.                          Keywords: OFDM, CEPS, Fairness, Rain Attenuation, Physical Layer